Arbitragem e a aplicação dos precedentes judiciais pelos árbitros no procedimento arbitral - Kairovsky, Marina (2018)
In the first work chapters, a brief historical sketch is presented on arbitration evolution, as well as its concept, discussing about arbitration basic notions and arbitration differences related to other institutes In the the work course, in its third chapter, the juridical nature of the arbitration and the jurisdiction are presented. Therefore, in the fourth chapter, theories on judicial precedents are presented in the Civil Code Procedure. Finally, in the fifth and last chapter, it is the arbitration procedure, from its initial considerations for arbitration procedure, through the arbitration award, request for enlightenment up to arbitration award the nullity, in which it must be verified whether the decisions made by the arbitrators are in conformity not only with the parties, but also with the legal order, on this account if the abritator´s decision is very unlike on what the legal order says, the arbitrator would be violating the universality of law principle